2008
DOI: 10.1007/s00125-008-1089-6
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilisation and costs associated with the treatment of diabetic foot ulcers. Prospective data from the Eurodiale Study

Abstract: Aims/hypothesis The aim of the present study was to investigate resource utilisation and associated costs in patients with diabetic foot ulcers and to analyse differences in resource utilisation between individuals with or without peripheral arterial disease (PAD) and/or infection. Methods Data on resource utilisation were collected prospectively in a European multicentre study. Data on 1,088 patients were available for the analysis of resource use, and data on 821 patients were included in the costing analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
193
4
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(220 citation statements)
references
References 20 publications
9
193
4
9
Order By: Relevance
“…The participants in the present study with a clinically suspected diabetic foot ulcer infection had poorer outcomes than reported in previously published studies, which enrolled people with various types of diabetic foot ulcers 5, 13, 14, 15. We found a 12‐month incidence of healing of 44.5%, while Prompers et al .…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…The participants in the present study with a clinically suspected diabetic foot ulcer infection had poorer outcomes than reported in previously published studies, which enrolled people with various types of diabetic foot ulcers 5, 13, 14, 15. We found a 12‐month incidence of healing of 44.5%, while Prompers et al .…”
Section: Discussioncontrasting
confidence: 58%
“…A lower perfusion grade suggests the presence of peripheral arterial disease, which previous studies have shown to be an important predictor of poor outcomes (i.e. lack of healing and lower extremity amputation) in people with a diabetic foot ulcer 5, 13, 14, 15. In the present study, among the five PEDIS domains, perfusion (indicating peripheral arterial disease) was shown to be the only independent predictor of healing.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations